Image Media to Improve Students Poetry Writing Skills in Elementary School - Julianto, Indra Rasyid; Saputro, Pramisdi Winanto; Hayati, Rifa'atussalwa; Gusvita, Widya; Sintasari, Diardana Prima (Lia Center of Research and Education, 2025)
This article aims to assist elementary school teachers in teaching poetry writing skills. Writing poetry is often perceived as a challenging process that requires considerable time to implement. Moreover, writing instruction in general is frequently seen as complex due to the various cognitive demands it places on students. One of the main challenges lies in the stigma that the creative writing process must integrate both linguistic and non-linguistic elements to contribute to the cohesion of a text in an academically sound manner. This study employs a qualitative descriptive approach, focusing on the use of visual media in poetry writing instruction through a literature review. The use of images can support students, particularly at the elementary level, by offering a more engaging and innovative learning experience. Based on the analysis of 10 literature sources, visual media significantly enhance students’ poetry writing abilities. Therefore, this method may serve as an effective alternative for teachers in the instructional process and as a means to cultivate literary appreciation.